Geobacillus and Bacillus Spore Inactivation by Low Energy Electron Beam Technology: Resistance and Influencing Factors - Zhang, Yifan; Moeller, Ralf; Tran, Sophia; Dubovcova, Barbora; Akepsimaidis, Georgios; Meneses, Nicolas; Drissner, David; Mathys, Alexander (Frontiers in Microbiology, 2018)
Low energy electron beam (LEEB) treatment is an emerging non-thermal technology that performs surface decontamination with a minimal influence on food quality. Bacterial spore resistance towards LEEB treatment and its influencing factors were investigated in this study. Spores from Geobacillus and Bacillus species were treated with a lab-scale LEEB at energy levels of 80 keV and 200 keV. The spore resistances were expressed as D values (the radiation dose required for one log10 reduction at a given energy level) calculated from the linear regression of log10 reduction against absorbed dose of the sample. The results revealed that the spore inactivation efficiency by the LEEB is comparable to that of other ionizing radiations and that the inactivation curves are mostly log10-linear at the investigated dose range (3.8 - 8.2 kGy at 80 keV; 6.0 - 9.8 kGy at 200 keV). The D values obtained from the wildtype strains varied from 2.2 - 3.0 kGy at 80 keV and 2.2 - 3.1 kGy at 200 keV. Bacillus subtilis mutant spores lacking α/β-type small, acid-soluble spore proteins showed decreased D values (1.3 kGy at 80 keV and 200 keV), indicating that spore DNA is one of the targets for LEEB spore inactivation. The results revealed that bacterial species, sporulation conditions and the treatment dose influence the spore LEEB inactivation. This finding indicates that for the application of this emerging technology, special attention should be paid to the choice of biological indicator, physiological state of the indicator and the processing settings. High spore inactivation efficiency supports the application of the LEEB for the purpose of food surface decontamination. With its environmental, logistical and economic advantages, LEEB can be a relevant technology for surface decontamination to deliver safe, minimally processed and additive-free food products.